Screening of antidepressant activity of nelumbo nucifera flower extract in mice - Preeti Shanbag; Ramdas Bhat; Sweta Prabhu; AR Shabaraya (Indian Journal of Pharmacy & Drug Studies, 2023)
Objective: To evaluate the anti-depressant activity of "Nelumbo nucifera" in experimental mice. Methods: The acute toxicity studies were conducted on fresh "Nelumbo nucifera" flower extract. The extract (100–200 mg/kg) was able to induce the mice's immobility duration in the Forced swimming and Tail suspension tests in a dose-dependent manner; the effects are comparable to those of popular drugs, such as Imipramine (10 mg/kg). Result: Both the lower dose (100mg/kg) and higher dose (200mg/kg) showed a dose-dependent significant decrease in depression. In line with Imipramine, our study found that the ethanolic extract of "Nelumbo nucifera" significantly (p>0.005) decreased immobility in both the tail suspension test and the forced swimming model of depression. These findings showed that "Nelumbo nucifera" exhibited in vivo effects that were selectively anti-depressant. Conclusion: The results of this study, in summary, revealed that "Nelumbo nucifera" ethanolic extract may have anti-depressant properties that make them potentially useful for treating patients with depressive disorders. However, more research is required to comprehend the mechanism of action and to pinpoint the key ingredient that produces anti-depressant-like activity.